The Influence Of Dıgıtal Learnıng Medıa Assısted By Google Arts And Culture On Students' Sbdp Learnıng Outcomes Class V SD Inpres 2 Tanamoındı - Miska Pratiwi; Andi Imrah Dewi; Kadek Hariana; Nashrullah; Kasmawati (Elementary Teacher Education Program, Majalengka University, 2026)
This study aims to determine the effect of using digital learning media assisted by Google Arts and Culture on the learning outcomes of Arts, Culture, and Crafts (SBDP) of fifth-grade students at SD Inpres 2 Tanamodindi. This study used a quantitative approach with a Pre-experimental method and a One Group Pretest-Posttest Design. The subjects were 28 fifth-grade students at SD Inpres 2 Tanamodindi. The data collection technique used a learning outcome test in the form of multiple-choice questions given before (Pretest) and after treatment (Posttest). The data obtained were analyzed using descriptive statistics, normality tests, and Normalized Gain (N-Gain) tests. The results showed an increase in student learning outcomes after the implementation of digital learning media assisted by Google Arts and Culture, as indicated by an increase in the average score from Pretest to Posttest and the results of the N-Gain calculation in the moderate to high increase category. Thus, it can be concluded that the use of digital learning media assisted by Google Arts and Culture has a positive effect on the SBDP learning outcomes of fifth-grade students at SD Inpres 2 Tanamodindi.